The changing perceptions of St. Lucian policing: how St. Lucian police officers view contemporary policing. (15th January 2021) - Stanislas, Perry
ABSTRACT: The article explores the changes in St. Lucian society and how they inform current policing attitudes and practice based on interviews with police officers. It critically outlines the history of policing in St. Lucia and provides evidence that challenges popular notions about colonial policing. The article examines how the rise in crime has exposed the fundamental failings of the Royal St. Lucian Police Force (RSLPF) and the changing nature of police work. It elucidates that the primary legacy of colonialism on the workings and practices of the RSLPF is a dysfunctional culture of supervision and management that adversely affects most aspects of policing and the ability to effectively fight crime.